Problems of Psychological Preparation of Children for School (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, the conflicts that arise during adolescence, the factors of their occurrence, the interests, needs, views, etc. between the parties in interpersonal relations. Problems such as the origin of conflicts and the emergence of conflicts based on these conflicts, as well as social empowerment and social empowerment are highlighted.